Principal Participatory Leadership Style, Organizational Culture, Teacher Achievement Motivation - Akbar, Islam Ali (Universitas Pamulang, 2023)
This survey aims to explore how the Participatory Leadership Style of Principals impacts organizational culture and teacher motivation achievement in Integrated Islamic Primary Schools located in Pondok Aren South Tangerang, Banten. The study involved 204 teachers, with 135 samples collected using a random sampling technique. A correlation technique using a questionnaire was used to analyze the data. The study revealed that there is a positive and significant relationship between the Participatory Leadership Style of Principals and teacher achievement motivation, as well as between organizational culture and achievement of teacher motivation. Moreover, there is also a positive and significant relationship between the Participatory Leadership Style of the principal and organizational culture together with teacher motivation achievement.